A terceirização e a perda da identidade profissional do trabalhador - Carvalho, Moisés Nepomuceno (2018)
This dissertation aims to study some key issues on contemporary labour law from a critical viewpoint on marked modifications taking place in society nowadays. In a larger dimension, the concepts, procedures and paradoxes of contemporary employment relationship regarding manpower outsourcing are examined to support a more specific discussion related to the recent legal interpretation and application of labour law in Brazil. The main strands of this discussion are two-fold: the first one is focused on conceptual and procedural premises of world of work and the second one is based on a subjective perspective about human labour. It is expected a debate about the complexity of labour relations and the difficulties faced in the application of labour law, and particularly, about the dilemmas that presently exist in a scenario marked by great changes in the Brazilian working practices. These changes are due to the so-called regulation of outsourcing, that plunders and slights the worker’s social rights and also blocks the creation of deep social bounds, essential to the establishment of a shared experience network.